An experimental investigation of the temperature effect on the mechanics of carbon fiber reinforced polymer composites. (18th January 2018) - Jia, Zian; Li, Tiantian; Chiang, Fu-pen; Wang, Lifeng
Abstract: Carbon fiber reinforced polymer (CFRP) composites are increasingly used in civil, naval, aerospace, and wind energy applications, where they can be frequently exposed to harsh temperature conditions and under static and dynamic loads. The extreme temperature conditions and dynamic loading are critical for CFRP composites structural design as the constituent polymer properties are highly sensitive to temperature and strain rate. This work experimentally investigates the effect of temperature, ranging from −100 °C to 100 °C, on the mechanical properties of CFRP composites under static and dynamic three-point bending tests. The results reveal that CFRP composites provide enhanced flexural strength, maximum deflection, and energy absorption at lower temperatures (−60 °C, −100 °C) while relatively poor performance at a higher temperature (100 °C). Experimental images from the post-mortem photographs, scanning electron microscopy, and high speed videos are implemented to observe various failure behaviors including microbuckling, kinking, and fiber breakage at different temperatures. Analytical modeling is further applied to reveal the underlying mechanisms responsible for these temperature dependent mechanical behaviors. The findings reported here provide insights into the study of the temperature effect on the mechanical response of CFRP composites, which expands the way to design stiffer, stronger and tougher CFRP composites.